High-power laser for periodontal surgery in a patient with Down syndrome: A case report (Research, Society and Development, 2021)
Individuals with Down's syndrome exhibit typical dental characteristics, which require specialized dental treatment. Additionally, due to the intellectual deficit, this management may be even more challenging. In this clinical case, we present a promising treatment proposal, using high power laser, in a 12-year-old boy with pericoronitis, who was unable to undergo periodontal surgery with other professionals. The use of this technique resulted in a brief and excellent postoperative care. We conclude that this clinical approach can be indicated for individuals with Down syndrome who have mild to moderate intellectual impairment.